Pengaruh Pendidikan Gizi Terhadap Pengetahuan dan Perilaku Ibu Tentang Gizi Seimbang Balita - Yuliana Salman; Niluh Reshi Widnyana Santi; Oklivia Libri (Jurnal Kesehatan Indonesia, 2020)
The prevalence of malnutrition in toodler in Indonesia is still high at 17.9% and stunting 35.6%. Lack of nutritional knowledge and health of parents, especially mothers is one of the causes of malnutrition in toodler. Nutrition education is an approach to produce individual or community behavior that is needed in maintaining balanced nutrition. This study aims to determine changes in knowledge and behavior of mothers after giving nutritional education. This research method was experimental with a pretest-posttest control group design. Statistical tests used the T test with 2 free samples on 80 samples that selected by probality sampling with simple random sampling technique. The results showed the control group of 10 respondents (25%) had good knowledge, increased to 13 respondents (33%) after 3 days without intervention, while the intervention group of 15 people (37%) had good knowledge, after 3 days given the intervention increased to 18 people (45%). Maternal behavior in control group had 17 respondents (43%) good behavior, increased to 22 respondents (55%), while the intervention group 22 people (55%) good behavior, increased to 24 people (60%) after giving nutrition education. There was a difference in knowledge between the control group and the intervention group (p = 0.001) and there were differences in maternal behavior between the control group who were not given nutrition education and the intervention group who were given nutrition education (p = 0.001).